Cross‐national patterns of substance use disorder treatment and associations with mental disorder comorbidity in the WHO World Mental Health Surveys. (2nd June 2019) - Harris, Meredith G.; Bharat, Chrianna; Glantz, Meyer D.; Sampson, Nancy A.; Al‐Hamzawi, Ali; Alonso, Jordi; Bruffaerts, Ronny; Caldas de Almeida, José Miguel; Cia, Alfredo H.; de Girolamo, Giovanni; Florescu, Silvia; Gureje, Oye; et al.
Abstract: Aims: To examine cross‐national patterns of 12‐month substance use disorder (SUD) treatment and minimally adequate treatment (MAT), and associations with mental disorder comorbidity. Design: Cross‐sectional, representative household surveys. Setting: Twenty‐seven surveys from 25 countries of the WHO World Mental Health Survey Initiative. Participants: A total of 2446 people with past‐year DSM‐IV SUD diagnoses (alcohol or illicit drug abuse and dependence). Measurements: Outcomes were SUD treatment, defined as having either received professional treatment or attended a self‐help group for substance‐related problems in the past 12 months, and MAT, defined as having either four or more SUD treatment visits to a health‐care professional, six or more visits to a non‐health‐care professional or being in ongoing treatment at the time of interview. Covariates were mental disorder comorbidity and several socio‐economic characteristics. Pooled estimates reflect country sample sizes rather than population sizes. Findings: Of respondents with past‐year SUD, 11.0% [standard error (SE) = 0.8] received past 12‐month SUD treatment. SUD treatment was more common among people with comorbid mental disorders than with pure SUDs (18.1%, SE = 1.6 versus 6.8%, SE = 0.7), as was MAT (84.0%, SE = 2.5 versus 68.3%, SE = 3.8) and treatment by health‐care professionals (88.9%, SE = 1.9 versus 78.8%, SE = 3.0) among treated SUD cases. Adjusting for socio‐economic characteristics, mental disorder comorbidity doubled the odds of SUD treatment [odds ratio (OR) = 2.34; 95% confidence interval (CI) = 1.71–3.20], MAT among SUD cases (OR = 2.75; 95% CI = 1.90–3.97) and MAT among treated cases (OR = 2.48; 95% CI = 1.23–5.02). Patterns were similar within country income groups, although the proportions receiving SUD treatment and MAT were higher in high‐ than low‐/middle‐income countries. Conclusions: Few people with past‐year substance use disorders receive adequate 12‐month substance use disorder treatment, even when comorbid with a mental disorder. This is largely due to the low proportion of people receiving any substance use disorder treatment, as the proportion of patients whose treatment is at least minimally adequate is high.